IMPLEMENTASI TEKNIK SELF MANAGEMENT UNTUK MEREDUKSI PERILAKU PROKRASTINASI AKADEMIK PADA MAHASISWA S1 - Khairunisa Khairunisa; A Muri Yusuf; Firman Firman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
One of the main tasks of students is learning because through learning students build critical abilities, add insight, improve the quality of knowledge, and hone their skills, namely social, psychological, affective, and cognitive abilities. Students are individuals who have an age range of 18-22 years. Referring to the developmental tasks at this phase, individuals should be able to take responsibility, commit, prioritize activities, manage themselves, and regulate the flow of their activities independently. However, the phenomenon of academic procrastination occurs in almost all students both outside and within the country so that this causes the behavior displayed by students to be contrary to the development that should be done. Academic procrastination is also caused by various factors, both internal and external. Academic perocrastination behavior also hinders individuals from achieving success in their academic life, such as decreased academic skills at school, late completion of lectures, and decreased quality of knowledge and insight in today's young generation.